Influenciador digital: comunicação nas redes sociais em tempos de individualismo - Baptista, Fernanda Daves Tonon (2022)
Introduction: The digital impacts the society and transforms all the ways of communication and relationships, creating opportunities for new activities in social media. Contextualize this moment through technologic and also the exacerbated individualism. Objective: characterize the digital influencers through their self-report and their ways of communication. Methodology: nonprobabilistic and intentional sample, composed per 45 women and 15 men, with average age of 39 years old. The included factors were: self-recognize as digital influencers and also have an active profile in social media platforms. The procedure was to apply an online questionnaire, elaborated by the researchers based on their self-professional experience, literature reference and also internet platforms. It had 24 closed and 2 opened questions, focused on the characterization of the digital influencers’s activities and on specifics aspects of their communication. The closed questions were applied on a statistical analysis. The results: majority of the group are women (73.3%), whom already works as digital influencers from 2 to 4 years (31.7%). Most of them considers it a profession, although only 56.7% has earnings from it. The main platform mentioned was Instagram (78.3%) and analysing the highlighted areas of activities, were detached: education (32%), beauty (25%), fashion (20%) and health (18%). Regarding the ways of communication, 46.7% quoted that they use their voices at high intensity, 55% uses emphasis and 48.3% uses informal vocabulary. It was observed some difficulties to understand the self-definition for their personas/images. About the future aspirations, it was observed that their goals are, in a descending order: be able to change life, to monetize their personal growth, to be a reference and to inspire people. Final conclusions: the main characteristics of the interviewed digital influencers were being able to receive earnings from that activity, the surprise of the initial and organic growth at the beginning and that they had Instagram as their main social media platform. The highlighted areas were education and beauty, the target audience is mostly composed by women, with age from 20 to 45 years old and their engagement comes mostly from likes and comments. Regarding communication, the main results were about the use of their voices at high intensity, deep voice, the use of emphasis and informal vocabulary. The impact of the digital transformation, brings us to raise questions about the liberty of the individuals in these new times, of the hypermodernity, which reveals itself the individualism society with major impacts in health - mental and physical - and in the society’s future as well